Measure for measure - Geckle, George L. (Shakespeare, the critical tradition., 2001)
In this critical evaluation of the classic, the discussion focuses on the nature of the major characters, the morality of their behavior, the conclusion of the play, and the genre of a play that was listed in the First Folio as a comedy. The contents of this volume cover texts by English, American and European scholars and critics including Malone, Stevens, Schlegel, Hazlitt, Coleridge, Hallam, Gervinus, Bagehot, Pater, Dowden, Furnivall, Swinburne, Symons, Boas, Shaw, Bradley, Chambers, Bridges, Masefield and Croce.